Examining debates on grammar correction in second language writing classes: Perspectives, challenges, and implications - Ny, Sun; Doung, Dara (Yayasan Mitra Persada Nusantara, 2023)
Writing in English is a fundamental productive skill for second-language (L2) learners, both inside and outside the classroom. Grammar correction plays a crucial role in fostering accuracy in writing; however, its effectiveness remains a topic of debate. This study reviews the arguments against grammar correction in L2 writing instruction. The research adopts a qualitative approach, relying entirely on secondary data. Existing studies, scholarly articles, and books on grammar correction in writing were systematically reviewed to extract key insights. Additionally, findings from previous research projects were analyzed to provide a comprehensive discussion. The analysis highlights the diverse perspectives on grammar correction, noting that its application largely depends on multiple factors, including instructional goals, learners' proficiency levels, and contextual settings. A critical issue identified is the role of instructors, whose expertise, adaptability, and teaching experience significantly influence the effectiveness of grammar correction. While some studies suggest that corrective feedback enhances learners’ grammatical accuracy over time, others argue that it can be discouraging and counterproductive. This review also presents theoretical arguments that challenge traditional grammar correction methods and proposes alternative approaches to enhance L2 writing instruction. The findings indicate that there is no one-size-fits-all answer to the debate. Whether grammar correction should be employed depends on specific teaching and learning contexts. Given the limitations of this review, which is solely based on document analysis, further empirical research using diverse methodologies is recommended. Future studies should investigate the long-term impact of grammar correction on L2 writing proficiency through experimental and mixed-method approaches.